COMPARATIVE STUDY OF THE CRITERIA OF ‘IBADURRAHMAN TAFSIR IBN KATSIR AND TAFSIR AL-MISBAH - Al Ghoni, Burhanudin; Azizah, Alfiyatul; Nurrohim, Ahmad; Dahliana, Yeti; Nirwana, Andi (Jurnal Asy-Syukriyyah, 2024)
'Ibadurrahman is an Arabic term that consists of two words: Ibad and Rahman. This term has been discussed in the tafsir of Ibn Kathir and Tafsir Al-Misbah according to their interpretation patterns. Tafsir Ibn Kathir and Tafsir Al-Misbah have different approaches to interpreting the Qur'an. Tafsir Ibn Katsir is known for its textual and historical approach, while Tafsir Al-Misbah uses a contextual and sociological approach. Comparing these two interpretations provides a broader and deeper insight into the criteria of 'Ibadurrahman. This research was carried out to address this problem. Using the comparative method, it is concluded that, as a whole, these two interpretations provide a comprehensive and complementary view of the criteria of 'Ibadurrahman, with different approaches but equally enriching understanding of Islamic teachings. The term ibadurrahman in the Qur'an refers to the character of humility (Tawadhu'), not arrogant, authoritative, gentle and always dhikr, which must be built with sincerity. Thus fostering urgency in life to achieve a noble position in the sight of Allah. The position of a servant on the side of Allah has a high position until Allah SWT praises their position as equal to the prophets and auliyya' then Allah relies on the attributes inherent in them in His great verse so that they are glorified with their position.